Dynamic tracing for epidermal growth factor receptor mutations in urinary circulating DNA in gastric cancer patients. Issue 2 (February 2017) - Shi, Xiu-Qin; Xue, Wen-Hua; Zhao, Song-Feng; Zhang, Xiao-Jian; Sun, Wukong
The mutations of epidermal growth factor receptor are detected in gastric cancer, indicating its suitability as a target for receptor tyrosine kinase inhibitors, as well as a marker for clinical outcome of chemotherapeutic treatments. However, extraction of quality tumor tissue for molecular processes remains challenging. Here, we aimed to examine the clinical relevance of urinary cell–free DNA as an alternative tumor material source used specifically for monitoring epidermal growth factor receptor mutations. Therefore, 120 gastric cancer patients with epidermal growth factor receptor mutations and 100 healthy controls were recruited for the study. The gastric patients also received epidermal growth factor receptor inhibitor treatment for a serial monitoring study. Paired primary tumor specimens were obtained with blood and urine samples, which were taken at a 1-month interval for a duration of 12 months. We found that urinary cell–free DNA yielded a close agreement of 92% on epidermal growth factor receptor mutation status when compared to primary tissue at baseline, and of 99% epidermal growth factor receptor mutation status when compared to plasma samples at different time points. Thus, our data suggest that urinary cell–free DNA may be a reliable source for screening and monitoring epidermal growth factor receptor mutations in the primary gastric cancer.